Improvement of Single-Switch Bridgeless PFC Cuk Converter for Circulating Current Elimination and Components Maximum Current Stress Reduction - Romai Noor, Mohamad Kamil; Ponniran, Asmarashid; JN, Jumadril; Abdul Rashid, Munirah Az Zahra; Naim Kasiran, Mohd Amirul; Yatim, Mohd Hafizie; Saiman, Suhaimi; Mat Said, Abdul Fatah (International Journal of Integrated Engineering, 2022)
This paper presents the improvement of a single-switch bridgeless PFC Cuk converter for circulating current elimination and maximum current stress reduction on components. Circulating current is eliminated by rearranging the position of input diodes thus the input diodes can block the returning path of current through the input inductors. The principle of circulating current elimination is also discussed in detail in this paper. A 100 W converter with an output voltage of -48 V has been tested to verify the principle. The results of the experimental hardware show the removal of the circulating current, the maximum current stress in input diodes is reduced from 8 A to 2.8 A and the maximum current stress in input capacitors also reduced from 11 A to 9.8 A.